Designing Entrepreneurial Competency Indicators for Coffee Farmers in Bandung Regency - Aji Pamoso; Lukman Z. Mohammad; Imanuddin Hasbi; Nuslish Jamiat (Journal Of Social Science (JoSS), 2025)
Coffee farmers in rural areas are typically smallholders who rely on traditional knowledge and demonstrate limited innovation, resulting in low productivity. Cultural and economic barriers, along with limited interest in education, further hinder farm performance. Entrepreneurial competencies such as innovation, creativity, and technical skills play a crucial role in improving this performance. This study aims to identify the dominant factors influencing the entrepreneurial competence of coffee farmers in Bandung Regency. A quantitative approach was employed using Exploratory Factor Analysis (EFA) to reduce 27 manifest variables into a set of latent factors. The instrument was developed based on three domains of entrepreneurial competence: opportunity identification, opportunity exploitation, and networking. A total of 270 coffee farmers were selected through purposive sampling. Data suitability was tested using Bartlett’s Test of Sphericity, the Kaiser-Meyer-Olkin (KMO) measure, and the Measure of Sampling Adequacy (MSA). Factor extraction was conducted using Principal Component Analysis with Varimax rotation. The analysis revealed five factors with eigenvalues greater than 1, explaining a cumulative variance of 66.637%. These factors are: (1) strategic business understanding, (2) social openness and adaptability, (3) institutional engagement and implementation, (4) planning and opportunity utilization, and (5) courage and innovation. These findings provide a foundation for developing more targeted and context-specific entrepreneurial competencies among coffee farmers